Translation dynamics of the plant-virus interaction. - Sans-Coll, Gemma; Castillo-Garriga, Araceli; Rodríguez-Bejarano, Eduardo; Merchante-Berg, Catharina (My University, 2023)
Tomato yellow leaf curl virus (TYLCV) causes a disease that gives rise to massive damage to tomato crops world-wide (Prasad et al., 2020). As a virus, it requires the host’s cellular machinery to be able to infect, which implies complex interactions between the virus and the plant. Understanding the translational machinery responsible for the production of viral proteins and, consequently, its ability to infect will allow to shed some light on these interactions and gain knowledge about the changes at the translational level that the plants experience upon infection, with the goal of finding potential targets for designing new defense strategies. To that end, the characterization of this interaction has been performed comparing the results of RNA-Seq on different fractions of polysome profiles, thus differentiating slightly translated genes from highly translated genes, of the infected vs. healthy plants. Furthermore, to deepen our knowledge on the regulatory mechanisms involved in the translational response, two isogenic tomato lines, one resistant (ty-5) and one susceptible (Santa Clara) to TYLCV, are being employed. ty-5 contains a recessive mutation located on the Pelota gene, which is involved in the recycling phase of the translation cycle (Lapidot et al. 2015), so the study of this mutant will inform about the role of the translational machinery in the viral infection. In addition, the local response in the phloem will be analyzed in the same manner using TRAP, generating transgenic tomato lines expressing a tagged version of RPL18B under a phloem-specific promoter. We will present the advances we have made regarding these objectives.
Keywords: Tomate - Virus - Congresos; Plagas - Congresos; Tomate; Virus